Human Trafficking and Security in Southern Africa The South African and Mozambican Experience - Iroanya, Richard Obinna (African Histories and Modernities, 2018)
This book investigates the links between human trafficking and national security in Southern Africa. Human trafficking violates borders, supports organised crime and corrupts border officials, and yet policymakers rarely view the persistence of human trafficking as a security issue. Adopting an expanded conceptualisation of security to encompass the individual as well as the state, Richard Obinna Iroanya lays the groundwork for understanding human trafficking as a security threat. He outlines the conditions and patterns of human trafficking globally before moving into detailed case studies of South Africa and Mozambique. Together, these case studies bring into focus the lives of the 'hidden population' in the region, with analysis and policy recommendations for combating a global phenomenon. .